Determinants of dividend policy inside the multinational firms / Nor Aishah Mohd Nor - Mohd Nor, Nor Aishah (2006)
This paper examines dividend policy for a sample of multinational firms listed on the Main Board and Second Board of Bursa Malaysia. The objective of this study is to identify which financial variables that influence the multinational firm's dividend payout in Malaysia. A sample of 25 firms was selected for the period 2000 to 2005 and the method used in this study is multiple regression analysis. The financial data of these companies was analyzed by regressing debt ratio, time interest earned, working capital ratio, tangibility, size, and return on equity to the dividend payout. Based on overall results, return on equity has a significantly positive relationship with dividend payout. Whereby, high return on equity tends to mean high dividend payments. This is because return on equity measures the common shareholder's rate of return on their investment in the company that is by looking at profitability of the firm relative to common equity. Investor will more interested to invest in the firm with high return on equity. The firms have to pay high dividend in order to maintain the shareholders as the firms relies on external financing (equity investor) to support growth.